Relationship between Body Mass Index and Complaints of Low Back Pain (LBP) on Online Motorcycle Taxi Drivers in Medan, Indonesia - Tamar Roganda Sitorus; Erin Christ Veronika A. Lubis; Rico Alexander (Eureka Herba Indonesia, 2023)
Low back pain is one of the musculoskeletal conditions caused by a lack of exercise. Worldwide, 37 percent of cases of LBP are related to occupational variables, including prolonged standing or exposure to vibration. Healthcare workers, drivers, and construction workers are also more susceptible to LBP. The purpose of this study was to determine the relationship between body mass index (BMI) and complaints of low back pain on online motorcycle taxi drivers in Medan. This study is an observational study, and as many as 97 respondents participated in this study. Data analysis was carried out with SPSS version 25, where univariate and bivariate analyses were performed. Correlation between body mass index and complaints of LBP, where there is a low correlation and statistically different. An increase in body mass index will tend to be followed by an increase in LBP complaints, although the correlation between the two is low. There is a relationship between body mass index and complaints of low back pain on online motorcycle taxi drivers in Medan, Indonesia.